Hybrid Strategy Study: The Role of Entrepreneurial Orientation and Total Quality Management in MSMEs - Timotius FCW Sutrisno; Junko A Effendy; Maria D G Prathivi (Jurnal Manajemen dan Kewirausahaan, 2019)
Entrepreneurial Orientation (EO) and Total Quality Management (TQM) are often referred to as antecedents of growth, competitive advantage and business performance by previous research. This research is the first investigation in a literature study that attempts to show the relationship between EO and TQM concepts on business performance. In this study, we use a multidimensional model on EO and TQM concepts and test a series of hypotheses related to business performance using student business data surveys in the MSMEs scale of Surabaya, East Java. It is expected that the results of this study can answer prepositional questions, whether the two strategies can help improve the performance of MSME-scale businesses in developing countries.https://doi.org/10.26905/jmdk.v7i2.3057